Cartridge based nucleic acid amplification test negative in highly suspected case of tuberculosis: a case report - Moradiya, Kalpesh; Muley, Arti; Kumar, Sunil; Patel, Kinjal; Mahida, Harshal (International Journal of Research in Medical Sciences, 2020)
Diagnosis of pulmonary tuberculosis is challenging till today. Smear microscopy is the easiest, commonest and widely employed tool for confirmatory diagnosis of pulmonary tuberculosis, but it has low sensitivity and specificity. Sputum culture can increase the diagnostic yield by 20-40%, but it takes long duration of 2-8 weeks to give result. The role of newly introduced cartridge based nucleic acid amplification test (CBNAAT) in the revised national TB control program (RNTCP) is highly promising with a higher yield of bacteriological diagnosis in sputum negative pulmonary tuberculosis patients with detection of rifampicin resistance rapidly. However, it also has some limitations which may result in false negative results. Case of a 50- year-old-male was reported who was initially managed for community-acquired pneumonia in view of negative sputum and CBNAAT but was later confirmed to have TB but by then he had developed cavities in lung and had transmitted the infection to his son.